Speed prediction system for reducing the time and fuel consumption using Adaptive Traffic Light Timer Control(ATLTC) - et. al., Niharika B.C, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traffic on roads had been a big problem since the automotive vehicles were launched to the market. Their main objective was for long distance travelling but now a days it became an essential part in our lives. Which in turn raised to many problems. This work presents a detailed overview of how we were able to reduce the effects of traffic that are time delay, fuel consumption air, pollution and sound pollution. Even though there are many ways to control traffic we are still unable to resolve problems due to heavy traffic. We are introducing new system which will be able to reduce the effects of traffic. We will be accomplishing this idea with the usage of Adaptive Traffic Light Timer Control (ATLTC), navigation system.